Pembelajaran Kooperatif Dan Kolaboratif Perspektif Pendidikan Islam - Mukhtar, Masrizal (Ameena Journal, 2023)
This research was conducted to discuss cooperative and collaborative learning from the perspective of Islamic education. This is a qualitative study with data collection techniques through literature review. The results show that cooperative and collaborative learning are teaching methods that place students in groups to achieve predetermined learning goals. In cooperative learning, students work in specific groups to achieve these goals. In collaborative learning, students also work in groups but with discussions, sharing, debates with conducive opinions that enrich insights, and mutual help to solve complex problems. To implement effective cooperative and collaborative learning, it is necessary to create a classroom environment with a constructivist perspective. This means that students are not seen passively, but actively involved in learning, and they bring their concepts into learning situations. Learning prioritizes the active process of students constructing meaning, often through interpersonal negotiation. Knowledge is not "out there", but is constructed personally and socially. In addition, teachers bring their concepts into learning situations, not only in terms of their knowledge but also their views on learning and teaching, which can affect their interactions with students in the classroom.